REGULATION OF REGISTRATION OF TRANSFER OF RIGHTS TO LAND DUE TO INSTRUCTION IN THE PERSPECTIVE OF PERMEN ATR/ KBPN NUMBER 16 YEAR 2021 - Elizabeth Marchia Aristha (NOTARIIL Jurnal Kenotariatan, 2023)
This paper analyzes the Registration Arrangements for the Transfer of Land Rights Due to Inheritance. The focus of the study in this paper is on the regulation of the registration of the transfer of land rights due to inheritance in the perspective of Permen ATR/KBPN Number 16 of 2021. The research method used in this paper is a normative research method using the Law, Concept, and Comparative Approach. Law. The analysis of legal materials in this paper is carried out using several legal theories, namely the theory of benefit, the theory of legal protection, and also the theory of legal certainty as an analytical tool in discussing legal issues in this study. It can be concluded that the regulation of land registration due to inheritance which was originally regulated based on the division of population groups as determined by the Regulation of the State Minister of Agrarian Affairs/Head of the National Land Agency Number 3 of 1997 has now been amended as based on the Regulation of the State Minister of Agrarian Affairs/Head of the National Land Agency Number 16 of 1997. 2021 which abolishes the provisions on the division of population groups in the land registration process due to inheritance in Indonesia. The legal materials used are primary legal materials in the form of laws and regulations relating to the formulation of the issues raised, then secondary legal materials in the form of reputable journals and the latest literature. Based on the results of the analysis, it is found that there is an inconsistency of norms in the land registration process due to inheritance, which can be seen in Article 111 Paragraph (1) letter c of the Minister of ATR/KBPN Number 16/2021 which does not guarantee legal certainty and still causes multiple interpretations in its implementation.